THE EFFECT OF EXTRACTION TIME ON THE PHYSICOCHEMICAL CHARACTERISTICS AND ANTIOXIDANT POTENTIAL OF AVOCADO WASTE OIL PRODUCED BY THE SOXHLETATION METHOD - Dyah Widowati; Artini Pangastuti; Setyaningrum Ariviani (Jurnal Teknologi Pertanian, 2022)
The avocado peels and seeds are potentially produced into vegetable oil through the soxhletation method. The soxhlet extracted oil characteristics are influenced by extraction time. The proper extraction time generated the oil standard characteristics. This research aimed to determine the effect of extraction time on yield, physicochemical characteristics, and antioxidant potential of avocado waste oil. The research was conducted through the extraction and characterization of avocado waste oil. This study used a Completely Randomized Design with one factor (extraction time: 4, 5, and 6 hours). An increase in extraction time caused an increase in yield and specific gravity, but the hydrolytic-oxidative stability and antioxidant potential were decreased. The 4 hours of extraction time was selected as the best treatment. The characteristics of avocado peel oil extracted for 4 hours were 6.25% of yield, 0.961 g/mL of specific gravity, 0.27% of free fatty acids (FFA), 0.44 mgKOH/g of acid value (AV), 0.98 mEq/kg of peroxide value (PV), 4.63 mEq/kg of p-Anisidine value (PAV), 8.86 mEq/kg of total oxidation (TOTOX), 68.786% of radical scavenging activity, and 523.96 mgTr/g of reducing power. The characteristics of avocado seed oil extracted for 4 hours were 4.59% of yield, 0.973 g/mL of specific gravity, 0.23% of FFA, 0.33 mEq/kg of AV, 0.48 mEq/kg of PV, 3.77 mEq/kg of PAV, 5.05 mEq/kg of TOTOX, 53.95% of radical scavenging activity, and 438.05 mgTr/g of reducing power. Altogether, avocado waste oil characteristics in each extraction time met the vegetable oil requirements and potentially developed in food industries.